INTERRELATION OF THE STAE AUTHORITY BODIES OF THE RUSSIAN FEDERATION SUBJECTS AND THE RUSSIAN FEDERATION GOVERNMENT IN THE FEDERAL LAWMAKING PROCESS - M. M. Kurmanov (Russian Journal of Economics and Law)
The article views the issues of the participation of legislative bodies of the Russian Federation subjects in the federal lawmaking process. The author investigates the main problems of their interaction with the Russian Federation government from the point of view of the Russian federalism development.